Prenatal and postnatal exposure to PFAS and cardiometabolic factors and inflammation status in children from six European cohorts. (December 2021) - Papadopoulou, Eleni; Stratakis, Nikos; Basagaña, Xavier; Brantsæter, Anne Lise; Casas, Maribel; Fossati, Serena; Gražulevičienė, Regina; Småstuen Haug, Line; Heude, Barbara; Maitre, Léa; McEachan, Rosemary R.C.; Robinson, Oliver; et al.
Highlights: PFAS mixture exposure was associated with higher HDL cholesterol and lower waist circumference. Postnatal PFAS were the main contributors to the identified mixtures. Prenatal PFOA was positively related with the pro-inflammatory biomarker IL-1beta. Abstract: Developing children are particularly vulnerable to the effects of exposure to per- and polyfluoroalkyl substances (PFAS), a group of endocrine disrupting chemicals. We hypothesized that early life exposure to PFASs is associated with poor metabolic health in children. We studied the association between prenatal and postnatal PFASs mixture exposure and cardiometabolic health in children, and the role of inflammatory proteins. In 1, 101 mothers-child pairs from the Human Early Life Exposome project, we measured the concentrations of PFAS in blood collected in pregnancy and at 8 years (range = 6–12 years). We applied Bayesian Kernel Machine regression (BKMR) to estimate the associations between exposure to PFAS mixture and the cardiometabolic factors as age and sex- specific z-scores of waist circumference (WC), systolic and diastolic blood pressures (BP), and concentrations of triglycerides (TG), high-density lipoprotein (HDL-C) and low-density lipoprotein (LDL-C) cholesterol. We measured thirty six inflammatory biomarkers in child plasma and examined the underlying role of inflammatory status for the exposure-outcome association by integrating the three panels into a network. Exposure to the PFAS mixture was positively associated with HDL-C and systolic BP, and negatively associated with WC, LDL-C and TG. When we examined the independent effects of the individual chemicals in the mixture, prenatal PFHxS was negatively associated with HDL-C and prenatal PFNA was positively associated with WC and these were opposing directions from the overall mixture. Further, the network consisted of five distinct communities connected with positive and negative correlations. The selected inflammatory biomarkers were positively, while the postnatal PFAS were negatively related with the included cardiometabolic factors, and only prenatal PFOA was positively related with the pro-inflammatory cytokine IL-1beta and WC. Our study supports that prenatal, rather than postnatal, PFAS exposure might contribute to an unfavorable lipidemic profile and adiposity in childhood.